Thermal processing of microalgae into biofuels and advanced energy materials - Chen, Wanru (2019)
Biomass is one of the potential alternatives to reduce the dependency on fossil fuels. Gaseous product and bio-oil generated from biomass can be used as fuels while bio-char can be used as a catalyst due to its highly porous structure and mineral-rich nature. In addition, some high nitrogen content biomass can result in the formation of nitrogen-doped carbon which can be employed as electrocatalysts for oxygen reduction reaction (ORR). In this study, algae (chlorella), with its renewable nature, easy accessibility and high nitrogen content, was chosen as the feedstock to produce bio-fuels as well as nitrogen-doped activated carbon. Firstly, the characterisation of chlorella was undertaken to show its characteristics. Inherently, chlorella has a carbon content of 50% and a relatively high nitrogen level (13.5%). During thermal decomposition, the main products are gaseous product, bio-oil and biochar. Gaseous product and bio-oil are normally used as renewable biofuels while biochar can be utilised as carbon materials. It is found that when temperature was raised to 500, 600, 700, 800 and 900 °C respectively, the yield of gaseous product kept increasing while the other two products dropped continuously. This observation can be attributed to the further cracking of long-chain hydrocarbons. The gaseous product mainly consists of CO, CO2, CH4, H2, and small amount of C2-C5 light hydrocarbons. Of those gases, CO and H2 accounted for more than 60 vol.%, which made chlorella a potential source for syngas production. Nickel-based catalysts were also introduced in this study to enhance the gas yield. It was found that 5Ni2Co /Ƴ-Al2O3 and 5Ni2Ce /Ƴ-Al2O3 could slightly improve the gas yield but deactivated quickly. Bio-oil was derived from mainly fatty acids and esters in the algae, which were cracked to heavy polycyclic aromatic hydrocarbons (PAHs). At last, biochar presented small surface area with low porosity so that activation process was conducted to improve the properties. Secondly, chlorella was chemo-physically (chemically and physically) activated to synthesise nitrogen-doped carbon materials. The resultant nitrogen-doped activated carbon is of clustered particles with a high surface area (up to 1032 m2 g-1). It was found that chemicals, ZnCl2 and H3PO4, can increase graphitic degree of the carbon materials while CO2 activation can further reinforce disorder in the structure. Sample Z2-500-C900 achieved the highest surface area (83% mesopore), a relatively high ID/IG ratio of 0.91 and a relatively high graphitic nitrogen level (0.8%). Amongst all the catalysts of Zx and Px series, Z2-500-C900 was the most efficient sample in electron transfer in ORR. Moreover, the onset potential of Z2-500-C900 catalyst was lower than that of the Pt-C by only 70 mV, demonstrating great ORR activity and the superiority was mainly attributed to the large surface area, graphitic nitrogen and mesoporous area. In addition, the samples with high defect level have better ORR performance as there are more active sites for O2 adsorption and activation. Meanwhile, Z2-500-C900 and P1-500-C900 had better ORR performance because of the existence of sulphur in the N-doped carbon (S, N dual doping), which induced high density of active sites. Although the nitrogen-doped carbon materials showed better ORR performance than commercial activated carbon, it was inferior to 20%Pt-C. It is therefore desirable to raise the effective nitrogen species in this chlorella-derived carbon material. Thus, ultrasonication process was introduced to pretreat the chlorella. By removing a portion of lipids, the nitrogen content was raised by increased protein content. The lipid-removal process is similar with the algae-derived bio-diesel production process in industry. In addition to the enhanced nitrogen, the defects were also increased to provide more active sites for oxygen reduction reaction. It was found that the SZ1-500-C900 (2.7 mA cm-2) of SZx group achieved higher current density than Z2-500-C900, implying higher graphitic nitrogen could increase the limiting current density. On the contrary, SPx group did not perform better than Px group because the phosphorus-containing particles compromised the surface area. The electron transfer number (n) indicated all those nitrogen-doped carbon materials presented a mixed two-electron and four-electron pathways. Additionally, the presence of sulphur can induce polarization which caused strain and more active sites so that more O2 could be chemisorbed and reacted. Moreover, those nitrogen-doped carbon materials have better tolerance to methanol than commercial 20%Pt-C since Pt is easily oxidised and its carbon support can be corroded. In summary, chlorella can be used for the production of hydrogen-rich syngas and Ni-based catalysts are not effective to improve the gas yield. Through pyrolysis, the oil content in chlorella, fatty acids and esters, are mainly converted into PAHs. As for nitrogen-doped activated carbons (NACs), high surface area, high mesoporous area, high graphitic nitrogen and high defects level can provide more active sites for oxygen reduction reaction. The self-doped activated carbon from chlorella is an effective way to produce NACs with high nitrogen content. Ultrasonication process towards algal precursors is feasible to increase the nitrogen level and the defective sites in the NACs. In the meanwhile, lipid extracted is full of esters and fatty acids so it can be used to produce biofuels.